1985
DOI: 10.1128/mcb.5.7.1795
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale production of polyoma middle T antigen by using genetically engineered tumors.

Abstract: A recombinant plasmid containing a metallothionein promoter-polyoma middle T cDNA fusion was constructed and used to transfect NIH 3T3 cells. Transformed cells expressing middle T were injected into nude mice. Within 3 weeks, each mouse produced tumors containing middle T equivalent to that in 250 to 1,000 100-mm dishes of polyomavirus-infected cells. This middle T, partially purified by immunoaffinity chromatography, retained activity as measured by its ability to be phosphorylated in vitro. The combined appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Since the bands were not seen when extracts from 293 cells infected with wild-type adenovirus or affinity gel lacking antibody was used (not shown), these polypeptides are likely to be specifically associated with middle T antigen. Another reasonable source of middle T antigen is tissue from nude mice carrying tumors expressing middle T antigen as a cDNA from the metallothionein promoter (11). Coomassie blue staining showed that the tumor tissue was less rich in middle T antigen and the extent of purification was much lower.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the bands were not seen when extracts from 293 cells infected with wild-type adenovirus or affinity gel lacking antibody was used (not shown), these polypeptides are likely to be specifically associated with middle T antigen. Another reasonable source of middle T antigen is tissue from nude mice carrying tumors expressing middle T antigen as a cDNA from the metallothionein promoter (11). Coomassie blue staining showed that the tumor tissue was less rich in middle T antigen and the extent of purification was much lower.…”
Section: Resultsmentioning
confidence: 99%
“…Rabbit serum was prepared from animals immunized with small t antigen (12a). Finally, monoclonal antibody pAB 815 directed against middle T antigen was used to prepare an affinity gel by being coupled to Affigel 10 (Biorad) as described previously (11). The * Corresponding author.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of 14-2 cells with 1 ,M cadmium sulfate for 7 hr to induce the metallothionein promoter resulted in a 3-fold stimulation of immunoprecipitable PtdIns kinase activity (Fig. 2B, lanes 1 and 2), tyrosine kinase activity (data not shown), and MTAg (18).…”
mentioning
confidence: 83%
“…We used 14-2 cells, an NIH 3T3 cell line transformed with a MTAg cDNA expressed from a metallothionein promoter (18). 14-2 cells produce approximately the same amount of MTAg as do polyoma virus-infected cells and are morphologically transformed, as assayed by their ability to form foci and grow in soft agar (18). Immunoprecipitates of 14-2 cells using rabbit anti-T serum had 20 to 50-fold higher PtdIns kinase activity than parallel immunoprecipitates from nontransformed NIH 3T3 cells ( Fig.…”
mentioning
confidence: 84%
“…pPyLT-1, pPyMT-1, and pPyST-1 (13) were obtained from R. Kamen (Genetics Institute, Boston, MA). pTR880 (T.M.R., unpublished data), pTR890 (14), and pTR841 (15), which carry cDNAs for LTAg, MTAg, and STAg, respectively, were developed in this laboratory. NIH 3T3 and BALB/3T3 clone A31 cells were obtained from C. Scher (The Children's Hospital, Philadelphia, PA), and the 3T3-F442A mouse preadipocyte cell line was obtained from stocks derived from those described by Green Control retrovirus stocks, lacking T-antigen coding region, contain titers of -106 Neor cfu/ml.…”
Section: Methodsmentioning
confidence: 99%